MEME DI ERA DIGITAL DAN BUDAYA SIBER - murfianti, Fitri (Acintya, 2019)
Abstract The rapid dissemination of meme cannot be separated from the development of communication technology. Memes that circulate are not just a joke but a reflection of offline reality and presented with interesting visuals. Image processing technology encourages people to be more creative. This study focuses on the process of consumption, production, and distribution of internet memes and the formation of cyberculture because of these process by using the literature study method. In consuming this internet meme commodity, a "work of consumption" process is needed. When the audience consumes information, it also has a "work of production" .The effort when the audience consumes and reproduces these information is called "work in progress". In consuming internet memes, there are several underlying motives, namely entetainment motives, self-expression motives, socializing and community building mottives, and informativeness Motives. Today Meme internet develops into a new communication style as a form of participatory digital culture. Cyber culture that is formed is the result of the construction of virtual identities that combine to form a new cultureKeyword : Internet Meme, Digital Era, Cyberculture